Speech Recognition using HMM - et al., Kunal A. Shukla (International Journal of Control and Automation, 2019)
Speech enhancement deals with processing of noisy speech signals, aiming at improving their perception by human or their correct decoding by machines. Speech enhancement algorithms attempt to improve the performance of communication systems when their input or output signals are corrupted by noise. The presence of background noise causes the quality and intelligibility of speech to degrade. Here, the quality of speech refers how a speaker conveys an utterance and includes such attributes like naturalness and speaker recognize ability. Intelligibility is concerned with what the speaker had said, that is, the meaning or information content behind the words. Therefore, a noisy environment reduces the speaker and listeners ability to communicate. To reduce the impact of this problem speech enhancement can be performed. It is usually difficult to reduce noise without distorting speech and thus, the performance of speech enhancement systems is limited by the tradeoff between speech distortion and noise reduction.